Changing spaces of education : new perspectives on the nature of learning - Brooks, Rachel, 1971-; Fuller, Alison, 1957-; Waters, Johanna L. 1976- (Routledge, Taylor & Francis Group, 2012)
"In today's modern climate, education and learning take place in multiple and diverse spaces. Increasingly, these spaces are both physical and virtual in nature. Access to and use of information and communication technologies, and the emergence of knowledge-based economies necessitate an understanding of the plurality of spaces (such as homes, workplaces, international space and cyberspace) in which learning can take place. The spaces of policy making with respect to education are also being transformed, away from traditional centres of policy formation towards the incorporation of a wider range of actors and sites. These changes coincide with a more general interest in space and spatial theory across the social sciences, where notions of simultaneity and diversity replace more modernist conceptions of linear progress and development through time. This volume proffers a unique perspective on the transformation of education in the 21st century, by bringing together leading researchers in education, sociology and geography to address directly questions of space in relation to education and learning. This collection of essays: - examines the changing and diverse spaces and concepts of education (occurring simultaneously at different scales and in different parts of the world) - explores where education and learning take place - discusses how spaces of education vary at different stages (compulsory schooling, tertiary and higher education, adult education and workplace learning) - inspects the ways in which the meanings attached to education and learning change in different national and regional contexts"--Resumé vydavatele